Liriope spicata Creeping Lilyturf, Border-grass, Creeping Liriope, Liriope, Monkey-grass - Edward Gilman (EDIS, 2007)
This document provides an overview of Liriope spicata, commonly known as creeping lilyturf, border-grass, or monkey-grass. It describes the plant’s characteristics, including its dense, uniform cover, violet-blue flowers, and blue-black fruits. The plant is noted for its rapid spread by rhizomes, making it suitable for confined planting areas. It thrives in USDA hardiness zones 6 through 10 and prefers partial to full shade with well-drained soils. The document also highlights its moderate drought tolerance, minimal pest issues, and propagation methods. However, it cautions against using creeping lilyturf as an edging plant due to its invasive nature. Original publication date October 1999.